Stem Cell Oncology Proceedings of the International Stem Cell and Oncology Conference (ISCOC 2017), 1-2 December, 2017, Medan, Indonesia - Adeya Adella, Cut (Taylor & Francis, 2018)
Stem cell research is one of the fascinating areas of contemporary biology, but, as with many expanding fields of scientific inquiry, research on stem cells raises scientific questions as rapidly as it generates discoveries. Research on stem cell treatment continues to advance knowledge about how an organism develops from a single cell and how healthy cells replace damaged cells in adult organisms. The most important potential application of human stem cells is the generation of cells and tissues that could be used for cell-based therapies, especially oncology. The Faculty of Medicine, Universitas Sumatera Utara, collaborated with the center of excellence and innovation (Pusat Unggulan Inovasi /PUI). The Stem Cell center of the Universitas Sumatera Utara (USU) organized an International Conference. The International Stem Cell and Oncology Conference (ISCOC) 2017 was an comprehensive academic conference in the field of stem cell and oncology research and also tropical medicine and related scientific topics. We expect this conference will benefit academics and practitioners in the field of health sciences in Indonesia. During the two day conference, researchers presented the most recent discoveries in stem cell and oncology and also general medical topics, and served as well in establishing networking for joint researchers and collaboration among participants. The editors and the scientific committee would like to thank the participants and express their gratitude to Faculty of Medicine of the Universitas Sumatera Utara for their support to ISCOC 2017. Lastly, we are most indebted for the generous support given by Universitas Sumatera Utara, Medan, Sumatera Utara, Indonesia.